Sources of atmospheric acidity in an agricultural-industrial region of São Paulo State, Brazil - da Rocha, G. O.; Franco, A.; Allen, A. G.; Cardoso, Arnaldo Alves [UNESP] (Amer Geophysical Union, 2003)
[1] Surface-based measurements of atmospheric formic acid (HCOOH), acetic acid (CH3COOH), sulfur dioxide (SO2), hydrogen chloride (HCl), and nitric acid (HNO3) were made in central São Paulo State, Brazil, between April 1999 and March 2000. Mean concentrations were 9.0 ppb (HCOOH), 1.3 ppb (CH3COOH), 4.9 ppb (SO2), 0.3 ppb (HCl), and 0.5 ppb (HNO3). Concentrations in sugar cane burning plumes were 1160-4230 ppb (HCOOH), 360-1750 ppb (CH3COOH), 10-630 ppb (SO2), 4-210 ppb (HCl), and 14-90 ppb (HNO3). Higher ambient concentrations of SO2, HCl and HNO3 were measured during the burning season (May-November). Concentrations of SO2 and HCl increased during the evening, and of HCOOH and CH3COOH were lowest in the morning, with peak levels in the afternoon. Ratios obtained between different species showed either nighttime maxima (SO2/HCOOH, SO2/CH3COOH, SO2/HNO3, CH3COOH/HNO3, SO2/HCl and HCOOH/HNO3), daytime maxima (HCOOH/HCl, CH3COOH/HCl and HNO3/HCl), or no clear trends (HCOOH/CH3COOH). Correlation analysis showed that SO2 and HCl were primary emissions from biomass burning and road transport; HCOOH, HNO3 and CH3COOH were products of photochemistry; HCOOH and CH3COOH were emitted directly during combustion as well as from biogenic sources. Biomass burning affected atmospheric acidity on a regional scale, while vehicular emissions had greater impact in urban and adjacent areas. Atmospheric ammonia levels were insufficient to neutralize atmospheric acidity, which was mainly removed by deposition to the surface.
Keywords: organic acids; sulfur dioxide; hydrogen chloride; nitric acid; biomass burning; acidity